2022
DOI: 10.1155/2022/3554026
|View full text |Cite
|
Sign up to set email alerts
|

Influence the Graphene Filler Addition on the Tensile Behavior of Natural Kenaf Fiber‐Based Hybrid Nanocomposites

Abstract: In current centuries, emphasis has moved from previous resources and compounds to lightweight substances to generate softer, most effective components for particular needs. Using organic kenaf fibers with nanoreinforced epoxy polymers in a blended microbially nanocomposite can improve properties and be environmentally friendly. Adding graphene powder to the epoxy resin increases barrier and mechanical properties while maintaining rigidity without compromising toughness. To explore the impression of such parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The tensile strength and modulus of composites made of raw fibers and graphite fibers were significantly enhanced because there was a clearly better distribution of fillers throughout the polymer. 17 Wear characteristics of engineering materials are primarily influenced by material hardness, load, and speed; in addition, the operating temperature and condition also affect the wear behavior of materials. The polymer material plays a crucial role in the tribological behavior of fiber-reinforced polymer (FRP) composites, and addition of nano/micro-sized fillers significantly affects the wear properties of FRP composites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tensile strength and modulus of composites made of raw fibers and graphite fibers were significantly enhanced because there was a clearly better distribution of fillers throughout the polymer. 17 Wear characteristics of engineering materials are primarily influenced by material hardness, load, and speed; in addition, the operating temperature and condition also affect the wear behavior of materials. The polymer material plays a crucial role in the tribological behavior of fiber-reinforced polymer (FRP) composites, and addition of nano/micro-sized fillers significantly affects the wear properties of FRP composites.…”
Section: Introductionmentioning
confidence: 99%
“…Suresha et al found increased wear resistance and a considerable improvement in mechanical characteristics of epoxy-carbon composites. The tensile strength and modulus of composites made of raw fibers and graphite fibers were significantly enhanced because there was a clearly better distribution of fillers throughout the polymer …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation